2018
DOI: 10.1161/circep.117.005414
|View full text |Cite
|
Sign up to set email alerts
|

Transient Outward K + Current (I to ) Underlies the Right Ventricular Initiation of Polymorphic Ventricular Tachycardia in a Transgenic Rabbit Model of Long-QT Syndrome Type 1

Abstract: I heterogeneity creates both triggers and an arrhythmogenic substrate in LQT1. In the absence of I, I interactions with I and I promote EADs in the RV while prolonging action potential duration in the left ventricle. This heterogeneity of action potential enhances dispersion of refractoriness and facilitates conduction blocks that initiate pVTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…In contrast, the function and gating kinetics of various cardiac potassium channels are very similar in dogs, rabbits, and humans with I Kr and I Ks as main repolarizing ion currents in all three species (Varro et al, 1993;Nerbonne, 2000;Nerbonne and Kass, 2005;Jost et al, 2013), with slight inter-species differences: In humans and dogs-just as in most mammals-I to is formed of two distinct subtypes named as I to,fast and I to,slow -with fast and slow recovery from inactivation, determined by Kv3.4 and Kv1.4, respectively (Patel and Campbell, 2005) as opposed to rabbits, where I to,slow is the primary transient Kv current in the left ventricle (Fedida and Giles, 1991), while in the right ventricle I to, fast and its role in LQT1 related arrhythmogenesis has recently been confirmed (Choi et al, 2018). The repolarization capacity of rabbits and dogs is more robust than that in humans due to higher I K1 , I Kr , and I Ks current densities (Jost et al, 2013;Husti et al, 2015) ( Figure 1C).…”
Section: Choice Of Models: Species Differences In Repolarizing Currentsmentioning
confidence: 91%
“…In contrast, the function and gating kinetics of various cardiac potassium channels are very similar in dogs, rabbits, and humans with I Kr and I Ks as main repolarizing ion currents in all three species (Varro et al, 1993;Nerbonne, 2000;Nerbonne and Kass, 2005;Jost et al, 2013), with slight inter-species differences: In humans and dogs-just as in most mammals-I to is formed of two distinct subtypes named as I to,fast and I to,slow -with fast and slow recovery from inactivation, determined by Kv3.4 and Kv1.4, respectively (Patel and Campbell, 2005) as opposed to rabbits, where I to,slow is the primary transient Kv current in the left ventricle (Fedida and Giles, 1991), while in the right ventricle I to, fast and its role in LQT1 related arrhythmogenesis has recently been confirmed (Choi et al, 2018). The repolarization capacity of rabbits and dogs is more robust than that in humans due to higher I K1 , I Kr , and I Ks current densities (Jost et al, 2013;Husti et al, 2015) ( Figure 1C).…”
Section: Choice Of Models: Species Differences In Repolarizing Currentsmentioning
confidence: 91%
“…Therefore, in the core of the genesis of phase‐2 EADs, the activation and inactivation kinetics of I Ca,L generate the oscillations while the slow increase of I Ks [can be the slow increase of I Kr , such as in the condition of LQT1 (Choi et al, 2018)] competes with the window I Ca,L (and late I Na ) to bring the system into and out of the oscillatory regime. Other currents play auxiliary roles in facilitating the genesis and termination of EADs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing inward currents may reduce the occurrence of phase-2 EADs, which may be the reason that increasing I Ca,L conductance (e.g., Figure 6d) or I NCX (e.g., Figure 5e) can also reduce the propensity of phase-2 EADs. Therefore, in the core of the genesis of phase-2 EADs, the activation and inactivation kinetics of I Ca,L generate the oscillations while the slow increase of I Ks [can be the slow increase of I Kr , such as in the condition of LQT1 (Choi et al, 2018)] competes with the window I Ca,L (and late I Na ) to bring the system into and out of the oscillatory regime. Other currents play auxiliary roles in facilitating the genesis and termination of EADs.…”
Section: Mechanisms Of Phase-2 Eadsmentioning
confidence: 99%
“…Thus, it seems reasonable to speculate www.nature.com/scientificreports www.nature.com/scientificreports/ that the p.P888L polymorphism contributes to increase the expressivity of these syndromes. Finally, mathematical models and experiments in ventricular cardiomyocytes demonstrated that a large and slowly inactivating I to can paradoxically exacerbate occurrence of early afterdepolarizations (EADs) and EADs-related arrhythmias in large mammals including humans [39][40][41] . Indeed, by lowering the plateau voltage during the early phase 1 of the AP plateau, I to delays the subsequent activation of other slower time and voltage-dependent outward currents (mainly I Ks ), thus diminishing their contribution to repolarization reserve during phases 2 and 3 of the AP, and thereby facilitating EADs.…”
Section: Discussionmentioning
confidence: 99%